Sensing a Way Out of René Char's "Historian's Hovel" - Jennifer Pap (Studies in 20th & 21st Century Literature, 2023)
René Char, like many other twentieth-century writers, faced the dilemma of how to write adequately about historical atrocity, and key moments in his writing about violence display this. In the context of post-World War I disillusionment, rising Fascism, and post-World War II calculations of those who vied for power, he also criticized bad faith iterations of History. However, a number of texts in his Feuillets d’Hypnos ('Leaves of Hypnos,') published in 1946 and written during his participation in the Resistance, assert an alternative history in which aesthetic, ethical, and political experience were linked. With the post-war return to the usual order of political institutions, the practice of this alternative history ended, as Char had predicted. It has its afterlife in his writing, however, which posits the continued creation of a shared, common aesthetic experience. Jacques Rancière’s “dissensus” can helpfully illuminate this, in that it designates multiple moments when people make themselves seen or heard against the expectations of the societally controlling “distribution of the sensible.”
Keywords: René Char; French Resistance; fascism; poetry; ethics; appearance; imagination; Hannah Arendt; Jacques Rancière; dissensus; Davide Panagia; sensation; childhood